algebra

posted by .

Reduce answers to lowest terms.
1.) 2x/2x^2+5x-3 + 5/x^2-9 =
2.) x-3/12x^3-18x^2 - x+1/16x^2-24x =
3.) 2x/x^2-2x-15 - x-2/3x^2+9x =

  • algebra -

    Use parentheses to isolate numerators and denominators. For example,
    3.) 2x/(x^2-2x-15) - (x-2)/(3x^2+9x)
    = 2x/[(x-5)(x+3)] + (x-2)/[3x(x+3)]
    = [1/(x+3)][2x/(x-5) + (x-2)/(3x)]

  • algebra -

    2/a-b+3/a+b

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra

    checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4) + (-1)*3x + (-1)*(-4) = 6x*3x = 18x^2 6x*-4 = -24x -1*3x = -3x -1* -4 = 4 18x^2 – 24x -3x +4 = 18x^2 – 27x + 4
  2. algebra

    24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3-12x check this problem for me please
  3. algebra

    -12x^6+24x^5-18x^2/-6x^2 3x^4+x^3-3x check see if I did it right.
  4. algebra

    -12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x could some one check this for me please
  5. math

    sums and differences of a rational algebraic expression 3/a + 2/ab + 1/abc another is 2x-1/6 + x+3/12 another is 2/a-b + 3/a+b another is 2a+b/a+b - 2a-b/a-b - 3a^2-b^2/a^2-b^2 another is 2x/2x^2+5x-3 + 5/x^2-9 another is x-3/12x^3-18x^2 …
  6. algebra

    reduce the fraction 6x/12x to lowest terms.
  7. algebra

    reduce the fraction 6x/12x to lowest terms
  8. calculus

    i need to find the derivative using chain rule: (x^2 + 2x - 6)^2 (1-x^3)^2 i got the answer from a site but the problem is i cannot get my work to match up with the answer, i don't know what im doing wrong. answer: 10x^9 + 36x^8 − …
  9. Math

    (2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+28x+21 =24x^3+18x^2-88x+21 <-- my answer but the correct answer is 24x^3-50x^2-23x+21 please correct me?
  10. 9th grade algebra (completing square)

    Can you check the following? A1. (2x + 3)^2 = 25 sqrt(2x + 3)^2 = +-sqrt(25) 2x + 3 = +- 5 2x + 3 = 5, 2x + 3 = -5 2x = 2, 2x = -8 x = 1, x = -4 {-4, 1} A2. x^2 + 14x + 45 = 0 x^2 + 14x + __ = -45 + __ x^2 + 14x + 49 = -45 + 49 (x

More Similar Questions